Scientific approaches for non-monsoon flow revival in Kanari river - Trivedi, Ayushi; Awasthi, Manoj Kumar (Indian Farming, 2022)
The long term consequences of overexploitation of the river and cutting flows affect a river and its surroundings. In this context, the river Kanari is already overexploited. Our suggestion is that since the lean season use is mainly for agriculture, therefore restoration of flow in water through short rivers can be accomplished by water harvesting,more efficient agricultural practices like drip irrigation and by moving more water-intensive agriculture (for example for rice and sugarcane) to water surplus areas.